PEMIKIRAN DAN GERAKAN ISLAM FUNDAMENTALIS - Moh Syaeful Bahar; Rofii Ali (KASBANA, 2021)
Fundamentalism is a religious ideology that emphasizes the existence of divinely revealed texts as they are. So that the term fundamentalist is equated with scripturalist because the religious rituals refer to the text rigidly. Etymologically the term fundamentalism in Islam has no equivalent, but in a historical perspective the movement is identical with the khawarij with its takfiri idiom. Indonesia is one of the countries where the ideology of fundamentalism has spread, infiltrating the domestic and public spaces of government and social organizations both personally and communally.